2021
DOI: 10.1016/j.ijcha.2021.100808
|View full text |Cite
|
Sign up to set email alerts
|

Common genetic variation in circadian clock genes are associated with cardiovascular risk factors in an African American and Hispanic/Latino cohort

Abstract: Misalignment of the internal circadian time with external physical time due to environmental factors or due to genetic variantion in circadian clock genes has been associated with increased incidence of cardiovascular risk factors. Common genetic variation in circadian genes in the United States have been identified predominantly in European ancestry individuals. We therefore examined the association between circadian clock single nucleotide polymorphisms (SNPs) in Clock, Cry1, Cry2, Bmal1 and Per3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Moreover, the importance of the rs1801260 polymorphism with MetS risk was observed in the Asian subgroup rather than in the Caucasian and Hispanic subgroups in stratified analysis. The C allele was an independent risk factor for potential insulin resistance in Asian patients with essential hypertension [ 31 ] and diabetes [ 36 ], while in Caucasian patients was positively associated with hypertension and coronary artery disease and negatively with obesity [ 27 , 37 , 38 ]. Monteleone et al [ 12 ] noted that the rs1801260 genotypes were not linked with obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the importance of the rs1801260 polymorphism with MetS risk was observed in the Asian subgroup rather than in the Caucasian and Hispanic subgroups in stratified analysis. The C allele was an independent risk factor for potential insulin resistance in Asian patients with essential hypertension [ 31 ] and diabetes [ 36 ], while in Caucasian patients was positively associated with hypertension and coronary artery disease and negatively with obesity [ 27 , 37 , 38 ]. Monteleone et al [ 12 ] noted that the rs1801260 genotypes were not linked with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies revealed a discrepancy in the association of CLOCK rs6850524 polymorphism and MetS risk factors, this meta-analysis observed no association. However, some studies found an increased risk for hypertension [ 37 ] and obesity [ 22 , 29 ] associated with rs6850524. Still, additional studies are needed to investigate the molecular mechanism involved.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have shown that BMAL1 gene polymorphisms are associated with the risk of developing type 2 diabetes in adults. 13 15 However, studies have noted that BMAL1 gene polymorphisms are not associated with the occurrence of type 2 diabetes in Japanese 33 and African-American 34 cohorts. In contrast to the findings of our study, Pappa et al showed that rs7950226 polymorphism of BMAL1 gene is associated with susceptibility to gestational diabetes in Greek pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have revealed the involvement of single nucleotide polymorphisms (SNPs) in the human Cry2 gene (hCry2) with prostate and breast cancer [20], Non-Hodgkin's lymphoma [21], hepatocellular carcinoma [22]. CRY2 gene polymorphism has also been shown to be associated with bipolar disorder [23], [24], depression [25], [26], attention-de cit/hyperactivity disorder (ADHD) [27], dysthymia [28], osteoporosis [29], diabetes [30]- [32], cardiovascular disorders [33], elevated blood pressure and hypertension, elevated triglyceride levels [34], dyslipidemia [30] and the more obvious, sleep disorder [35] as well as affective disorders [36].…”
Section: Introductionmentioning
confidence: 99%